High sensitivity methods to quantify chloroquine and its metabolite in human blood samples using LC–MS/MS. (15th March 2019) - Kaewkhao, Karnrawee; Chotivanich, Kesinee; Winterberg, Markus; Day, Nicholas PJ; Tarning, Joel; Blessborn, Daniel
Aim: Chloroquine is an antimalarial drug used in the treatment of Plasmodium vivax malaria. Three methods to quantify chloroquine and its metabolite in blood matrices were developed and validated.Methodology & results: Different high-throughput extraction techniques were used to recover the drugs from whole blood (50 μl), plasma (100 μl) and dried blood spots (15 μl as punched discs) followed by quantification with LC–MS/MS. The intra- and inter-batch precisions were below 15%, and thus meet regulatory acceptance criteria.Conclusion: The developed methods demonstrated satisfactory validation performance with high sensitivity and selectivity. The assays used simple and easy to automate extraction techniques. All methods were reliable with robust performance and demonstrated to be suitable to implement into high-throughput routine analysis of clinical pharmacokinetic samples.